Nazis und der Nahe Osten. - Küntzel, Matthias, author.
1 online resource.
Keywords: "Nazis, Islamic Antisemitism, and the Middle East demonstrates the impact on the Arab world of Nazi ideology and propaganda in the 1930s and beyond. In 1937, with the brochure "Islam and Judaism", a new form of Jew hatred came into the world: Islamic antisemitism. The Nazis did everything they could to anchor this new message of hate through their Arabic-language radio propaganda. The book sheds light on this hitherto unknown chapter of Germany's past. It presents new archive findings that show how the image of Jews in Islam changed between 1937 and 1948 under the influence of this propaganda and other Nazi activities. This fresh look at Middle East history allows for a more precise assessment of the present: What exactly is "Islamic antisemitism"? How is it currently manifesting itself in Germany and France? What makes it particularly dangerous? Only when we understand how strongly modern Middle East history is shaped by the aftermath of National Socialism will we be able to correctly interpret the hatred of Jews in this region and its echo among Muslims in Europe and develop adequate countermeasures. This volume will be of interest to those researching antisemitism, Nazi foreign policy, and the political history of the Middle East"--